Desain Mesin Pemisah Kulit Kacang Tanah Menggunakan Sistem Transmisi Ganda - Nanang Endriatno (Piston: Jurnal Teknologi, 2025)
Post-harvest processing of peanuts requires an efficient outer skin peeling process to speed up the production process. Manual peeling is still common among farmers and small business actors, but this method is considered less efficient in terms of time and energy. Therefore, this study aims to develop a peanut peeling machine using a double belt transmission mechanism to improve work efficiency and peeling results. The machine development method includes designing and mechanism design. The machine is designed with a steel angle frame measuring 800 mm high × 500 mm long × 500 mm wide, using a peeling roller with a diameter of 267 mm and a length of 450 mm consisting of four spoons. The roller functions to scrape the peanut skin through a pressing system, while the sieve keeps the seeds and skins still during pressing. The mixture of peanut skin and seeds that have been separated will fall together through the sieve. Then it passes through the blower and separation occurs. This machine is driven by a 5.5 HP electric motor with a maximum rotation of 1400 rpm. The transmission system uses two belts and pulleys: a 100 mm input pulley and a 250 mm output pulley produce a roller rotation of 560 rpm, while the blower is driven by a 100 mm input and output pulley at 1400 rpm. This machine has the potential to be a practical mechanical solution to increase the efficiency of peeling results on a small industrial scale. Further development is needed to build a physical prototype of the machine and evaluate its performance and efficiency.